(untitled) (British Journal of Global Ecology and Sustainable Development, 2025)
This article analyzes the developmental functions of laboratory classes from a scientific and pedagogical perspective. In the educational process, laboratory work is viewed not only as a means of consolidating theoretical knowledge but also as a tool for developing students’ thinking, fostering their creative abilities, and enhancing independent and critical thinking skills. Furthermore, the article highlights the role of laboratory classes in learner-centered education and their relevance in modern pedagogy.